A behavioral macroeconomic model with endogenous boom-bust cycles and leverage dynamcis - Lukas Scheffknecht; Felix Geiger (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2011)
We merge a financial market model with leverage-constrained, heterogeneous agents with a reduced-form version of the New-Keynesian standard model. Agents in both submodels are assumed to be boundedly rational. The fi nancial market model produces endogenously arising boom-bust cycles. It is also capable to generate highly non-linear deleveraging processes, fi re sales and ultimately a default scenario. Asset price booms are triggered via self-fulfilling prophecies. Asset price busts are induced by agents' choice of an increasingly fragile balance sheet structure during good times. Their vulnerability is inevitably revealed by small, randomly occurring shocks. Our transmission channel of financial market activity to the real sector embraces a recent strand of literature shedding light on the link between the active balance sheet management of financial market participants, the induced procyclical fluctuations of desired risk compensations and their final impact on the real economy. We show that a systematic central bank reaction on financial market developments dampens macroeconomic volatility considerably. Furthermore, restricting leverage in a countercyclical fashion limits the magnitude of financial cycles and hence their impact on the real economy.
urn:nbn:de:bsz:100-opus-6628
Keywords: E31; E41; E47; E52; 330; behavioral economics; New-Keynesian macroeconomics; monetary policy; agent-based financial market model; leverage; macroprudential regulation; financial stability; asset price bubbles; systemic risk